2021
DOI: 10.1002/mrm.29034
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of measurement precision in single‐voxel spectroscopy at 7 T: Toward minimal detectable changes of metabolite concentrations in the human brain in vivo

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…The SB WURST pulse was already successfully utilized in other MR spectroscopy sequences 14,40,41 but has – to our knowledge – not been used as an MB pulse before, neither in MR imaging nor in MRS. For SVS acquisitions, it was recently shown that the WURST pulse does not exhibit significant differences in the reproducibility of resulting metabolite concentrations and spectral shape analysis but allows for decreased peak power and reduced chemical shift displacement, compared to the HS pulse that is used by default in the SPECIAL sequence 24 . This is even more important for MB pulses because, in the simplest case, nearly twice the nominal peak power is needed to fulfill the adiabatic condition 20 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The SB WURST pulse was already successfully utilized in other MR spectroscopy sequences 14,40,41 but has – to our knowledge – not been used as an MB pulse before, neither in MR imaging nor in MRS. For SVS acquisitions, it was recently shown that the WURST pulse does not exhibit significant differences in the reproducibility of resulting metabolite concentrations and spectral shape analysis but allows for decreased peak power and reduced chemical shift displacement, compared to the HS pulse that is used by default in the SPECIAL sequence 24 . This is even more important for MB pulses because, in the simplest case, nearly twice the nominal peak power is needed to fulfill the adiabatic condition 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The sequence diagram for the 2SPECIAL sequence employing a WURST inversion pulse before the excitation is depicted in Figure 1A. Bloch simulations were performed taking the transmit magnetic field B 1 + as well as the off‐resonances ΔB 0 into account to evaluate the excitation profile performance and compare it to the MB HS pulse 23,24 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations